ICTs, growth, and environmental quality nexus: dynamic panel threshold regression - Yong, Sze Wei; Law, Siong Hook; Ibrahim, Saifuzzaman; W. Mohamad, Wan Norhidayah (Springer, 2022)
ICTs (information and communication technologies) have emerged as a potent new force. Digitalization, modernization, and automation of the manufacturing process are expected to facilitate ICT adoption, resulting in increased genuine environmental concerns. This research aims to examine the impact of ICTs on environmental quality and the relationship between ICTs, environmental quality, and economic growth. Dynamic panel threshold regression was employed, and the sample countries comprised 69 developing countries from 2010 to 2019. The threshold technique will identify the precise threshold value of ICTs and highlights the impacts of ICTs on the environmental quality nexus when above and below the threshold value in developing countries. Empirical evidence suggests that ICTs positively impact environmental quality (CO2) when above the ICTs threshold value. However, ICTs provide a positive but insignificant impact on environmental quality when below the ICTs threshold value of 4.699. Additionally, ICTs affect the economic growth and environmental quality nexus, with increasing economic growth resulting in a decrease in CO2 emissions in developing countries when ICTs are below the threshold value. Thus, the ICTs threshold value should be used to ensure that ICTs adoption promotes sustainable economic growth and resolves environmental degradation issues in developing nations.